Signal Transduction Pathway in Chronic Leukemia - Alenzi, Faris Q (Bangladesh Journal of Medical Science, 2017)
It is becoming progressively clearer that the three RAS genes, N-. H-and K-RAS, encode 21 kDa proteins which act as intracellular switches, playing important roles in the signal transduction pathway that control cell development and maturation. These three genes are profoundly homologous, yet more recent findings indicate they have important roles in the functions various cell types playing focal roles in numerous human infections. This article briefly reviews the regulation of RAs-dependent signaling mechanisms. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.21-23